Redox-switchable α-diimine palladium catalysts for control of polyethylene topology. (28th September 2019) - Mundil, Robert; Wilson, Lucy E.; Schaarschmidt, Dieter; Císařová, Ivana; Merna, Jan; Long, Nicholas J.
Abstract: A series of palladium complexes bearing ferrocene substituted α-diimine ligands was synthesized and investigated for ethene polymerization at different conditions to modulate the extent of "chain-walking" mechanism and regulate branching and topology of resulting polyethylenes. All ferrocene substituted complexes catalyzed living/controlled ethene polymerization. The ability of ferrocene substituted palladium complexes to provide polyethylenes with dendritic topology was proved by measuring their Mark-Houwink plots. In-situ chemical oxidation of ferrocene moieties via silver triflate was used to affect the catalyst electronic structure and support the "chain-walking" mechanism. Oxidation of palladium catalyst led to its destabilization while the catalytic activity of newly formed sites was substantially increased. It was demonstrated that catalyst oxidation is a powerful tool to regulate the topology of resulting polyethylenes. Graphical abstract: Image 1 Highlights: Newly synthesized Pd complexes with ferrocene substituted α-diimine ligands. All complexes provide living/controlled ethene polymerization. Chemical oxidation of Pd complexes gives more densely branched polyethylenes. Redox switch of Pd catalyst can regulate the PE topology.